Development and characterisation of lyophilised ethambutol-loaded polymeric nanoparticles - Kole, Eknath; Sonar, Yogesh; Sarode, Rahul J.; Chaudhari, Atul; Naik, Jitendra (Creative Pharma Assent, 2025)
Background: Tuberculosis (TB) remains a universal health crisis, requiring innovative drug delivery systems to overcome challenges like prolonged treatment duration and patient non-adherence. This study was designed to develop Ethambutol (ETH)-loaded poly-ε-caprolactone (PCL) nanoparticles (NPs) as a sustained-release pulmonary delivery platform for TB therapy. Methodology: ETH-PCL NPs were fabricated using the nanoprecipitation technique with Lutrol® F68 as a stabiliser. The formulation was optimised for physicochemical properties (particle size, polydispersity index (PDI), zeta potential), encapsulation efficiency (EE), and morphology (SEM). In vitro drug release and 3-month colloidal stability were evaluated. Results and Discussion: The optimised NPs exhibited a rod-shaped morphology with smooth surfaces, an average size of 426.3 ± 13.03 nm, PDI < 0.467, zeta potential of -18.8 ± 0.520 mV, and EE of 76.57±3.86%. Sustained ETH release (86.62% over 24 h) and robust colloidal stability (negligible changes in size, PDI, and zeta potential over 3 months) were achieved. The formulation's biodegradable PCL core and scalable design align with the need for cost-effective, patient-centric therapies. Conclusion: ETH-PCL NPs represent a promising nanocarrier platform for TB, combining sustained drug release, high encapsulation efficiency, and long-term stability. While in vitro results are encouraging, future studies must validate in vivo efficacy and pulmonary delivery potential. This work underscores the viability of nanotechnology in addressing TB treatment challenges, particularly in improving adherence and targeting mycobacteria-laden macrophages.